2013
DOI: 10.1007/s11481-013-9516-y
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Macrophage Biology by Lithium: A New Look at an Old Drug

Abstract: Lithium (Li) continues to be a standard small compound used for the treatment of neurological disorders. Besides neuronal cells, Li is also known to affect immune cell function. In spite of its clinical use, potential mechanisms by which Li modulates immune cells, especially macrophages and its clinical relevance in bipolar patients are not well understood. Here, we provide an overview of the literature with regard to Li's effects on monocytes and macrophages. We have also included some of our results showing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…This is because unlike traditional composite blends, where typically mechanically robust bioactive glass [26][27][28] or ceramic [29][30][31] expression increased, and iNOS and CD86 expression decreased under the influence of lithium release. Macrophage proliferation was somewhat reduced in the lithium groups, which is consistent with previous work on macrophage response to lithium [17]. While lithium has been universally described to be affecting physiological changes through its suppression of GSK3β [16,32,33], its immunomodulatory anti-inflammatory effects have been alternately attributed to the activation of transcription factor CREB [33].…”
Section: Discussionsupporting
confidence: 87%
“…This is because unlike traditional composite blends, where typically mechanically robust bioactive glass [26][27][28] or ceramic [29][30][31] expression increased, and iNOS and CD86 expression decreased under the influence of lithium release. Macrophage proliferation was somewhat reduced in the lithium groups, which is consistent with previous work on macrophage response to lithium [17]. While lithium has been universally described to be affecting physiological changes through its suppression of GSK3β [16,32,33], its immunomodulatory anti-inflammatory effects have been alternately attributed to the activation of transcription factor CREB [33].…”
Section: Discussionsupporting
confidence: 87%
“…One also needs to acknowledge the problem of important potential confounding, and some potentially moderating, factors such as smoking, BMI, medical comorbidities, level and type of psychopathology, genetic heterogeneity, sample collection and processing, time of day, type of assay employed and how long samples are stored before being analyzed. [73][74][75][76][77][78] Subjects were medicated in the majority of studies included in the present analysis. There is evidence that antipsychotics (as a class) increase sIL-2R and decrease IL-1β and interferon-gamma (IFN-γ) levels in the blood in patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, wear debris activate the MAPK pathway in bone marrow-derived macrophages, promoting the differentiation of osteoclast precursor cells 46. Furthermore, it has been reported that LiCl significantly suppressed LPS-induced activation of ERK phosphorylation in macrophages 47,48. Thus, MAPK pathway targeting has the capacity to regulate the two key processes resulting in aseptic loosening: wear particle-induced inflammation and osteoclast formation.…”
Section: Discussionmentioning
confidence: 99%